Mortality of critically ill patients with severe influenza starting four years after the 2009 pandemic. Issue 11 (2nd December 2019) - Vandroux, David; Allyn, Jérôme; Ferdynus, Cyril; Gaüzere, Bernard-Alex; Kerambrun, Hugo; Galas, Thomas; Allou, Nicolas; Persichini, Romain; Martinet, Olivier; Jabot, Julien
Abstract: Background : In Reunion Island, influenza is not considered a serious illness despite significant mortality in intensive care unit (ICU). We assess the post-pandemic mortality of influenza by comparing it to other community-acquired pneumonia in our ICU. Methods : Retrospective, descriptive, and single-centre cohort study. The main aim was to determine the standardized mortality ratio (SMR) for influenza based on the quartiles of the SAPSII score in the reference population of 954 patients hospitalized for community-acquired pneumonia. Another aim was to analyze the risk factors for mortality in influenza patients. Results : 127 consecutive patients were hospitalized in our ICU with a positive influenza PCR, from January 2013 to December 2017. The mortality rate of these patients was 31% (CI 95%: 23–39%). In patients hospitalized for community-acquired pneumonia, the SMR of patients with influenza was 1.24 (CI 95%: 0.89–1.70). At admission, thirty-nine patients (31%) had superinfections, in 17 caused by methicillin-susceptible Staphylococcus aureus . Need for renal replacement therapy (RR 2.53 [1.29–4.93]) or ECMO (RR 2.35 [1.16–4.74]) were associated with mortality. Twenty-four patients underwent ECMO, 17 with VV-ECMO. Conclusions : Mortality in patients with influenza pneumonia was higher than the expected mortality in community-acquired pneumonia. Although generally considered benign, influenza is a deadly infection in ICU patients in Reunion Island.